Reduced Sensitivity to Between-Category Information but Preserved Categorical Perception of Lexical Tones in Tone Language Speakers With Congenital Amusia - Chen, Fei; Peng, Gang (Frontiers in Psychology, 2020)
Previous studies have shown that for congenital amusics, long-term tone language experience cannot compensate for lexical tone processing difficulties. However, it is still unknown whether such difficulties are merely caused by domain-transferred insensitivity in lower-level acoustic processing and/or by higher-level phonological processing of linguistic pitch as well. The current P300 study links and extends previous studies by uncovering the neurophysiological mechanisms underpinning lexical tone perception difficulties in Mandarin-speaking amusics. Both the behavioral index (d′) and P300 amplitude showed reduced within-category as well as between-category sensitivity among the Mandarin-speaking amusics regardless of the linguistic status of the signal. The results suggest that acoustic pitch processing difficulties in amusics are manifested profoundly and further persist into the higher-level phonological processing that involves the neural processing of different lexical tone categories. Our findings indicate that long-term tone language experience may not compensate for the reduced acoustic pitch processing in tone language speakers with amusia but rather may extend to the neural processing of the phonological information of lexical tones during the attentive stage. However, from both the behavioral and neural evidence, the peakedness scores of the d′ and P300 amplitude were comparable between amusics and controls. It seems that the basic categorical perception (CP) pattern of native lexical tones is preserved in Mandarin-speaking amusics, indicating that they may have normal or near normal long-term categorical memory.